2018
DOI: 10.1002/epi4.12251
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic inhibition: A novel approach toward controlling neuronal excitability and seizures

Abstract: SUMMARYConventional antiseizure medications reduce neuronal excitability through effects on ion channels or synaptic function. In recent years, it has become clear that metabolic factors also play a crucial role in the modulation of neuronal excitability. Indeed, metabolic regulation of neuronal excitability is pivotal in seizure pathogenesis and control. The clinical effectiveness of a variety of metabolism-based diets, especially for children with medication-refractory epilepsy, underscores the applicability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…When administered, 2DG competes with glucose as substrate for glycolysis in cells with a high energy demand. 2DG also blocks the glycolytic pathway since 2DG-6P cannot be further converted by phospho-glucose isomerase, resulting in inhibition of glycolysis [52]. It has been shown that the addition of 2DG reversibly reduces burst frequency after in vitro excitatory stimulation of hippocampal CA3 neurons [53].…”
Section: Biochemistry Of Kd Actionmentioning
confidence: 99%
“…When administered, 2DG competes with glucose as substrate for glycolysis in cells with a high energy demand. 2DG also blocks the glycolytic pathway since 2DG-6P cannot be further converted by phospho-glucose isomerase, resulting in inhibition of glycolysis [52]. It has been shown that the addition of 2DG reversibly reduces burst frequency after in vitro excitatory stimulation of hippocampal CA3 neurons [53].…”
Section: Biochemistry Of Kd Actionmentioning
confidence: 99%
“…This finding has been suggested to underpin the effect that ketogenic diets can have to reduce risk propensity to epileptic seizures (75). As such, treatment with inhibitors of glycolysis including 2-deoxy-D-glucose has recently been suggested as a route towards effective seizure management (76). The rationale for such treatments is based on the observation that inhibition of glycolysis suppresses network excitability and epileptiform bursting both in vivo and in hippocampal slices (77)(78)(79), which complements the results we present here showing that glucose depletion decreases synchronous bursting frequency in cultured networks and that this can potentially be attributed to glycolytic cessation.…”
Section: Discussionmentioning
confidence: 97%
“…In our work, the injection of 2-DG was i.c.v., directly inhibiting glycolysis in brain cells and causing chronic energy deficiency in the brain. In contrast, studies showing the protective role of 2-DG treatment (Shao et al 2018;Rho et al 2019) used i.p. drug administration, causing a concurrent and significant rise of both blood glucose level and cerebral blood flow, as has been reported for both animals (Combs et al 1986;Breier et al 1993;Horinaka et al 1997;Koenig et al 2019;Leiter et al 2019) and humans (Landau et al 1958;Elman et al 1999).…”
Section: Discussionmentioning
confidence: 98%